Com a palavra, o povo Haliti : uma análise do léxico em português na narrativa do documentário “Haliti Paresi - origem, história e ascensão" - Luz, Antonia Cristina Valentim da (2024)
Among the indigenous peoples of Mato Grosso, this thesis focuses on the Haliti people, also known as the Paresi, who live in a region near Cuiabá. Their native language is Haliti, which belongs to the Arawak language family, and most of the population is bilingual. Thus, this work falls within the perspective of Multidisciplinary Applied Linguistics, adopting a theoretical-methodological hybridity to study the Portuguese lexicon recorded in the contemporary narrative present in the documentary "Haliti Paresi: Origin, History, and Ascension." Accordingly, the general objective is to analyze the lexicon of the Portuguese language narrative recorded in the documentary's narrative from the perspective of onomasiology. The investigation began with the study of the canonical structure of narrative by Labov and Waletzky (1967), Labov (1972), followed by the narrative analysis by Bastos and Biar (2015) based on Sacks (1984), Garcez (2001), and Mishler (1986, 2002). It concluded with the theoreticalmethodological foundations of Onomasiology represented by the Rational System of Concepts by Hallig and Wartburg (1963) and Coseriu's (1977) theory of lexical fields. In conclusion, the lexemes used by the Haliti people reflect non-indigenous influences; however, they do not pose a threat to their language and culture. On the contrary, these influences have been re-signified and have become tools in their struggle for rights and in the realization of their projects.